ORCHESTRA AS A CREATIVE LABORATORY OF MUSICAL CONDUCTING: NEW EDUCATIONAL TECHNOLOGIES - Sabina Miskinova (Bright Mind Publishing, 2025)
In the modern educational space, the orchestra is considered not only as a form of artistic and performing practice, but also as a creative laboratory in which new approaches to musical conducting are formed. The article analyzes innovative educational technologies that allow integrating collective music-making with digital instruments, multimedia platforms and interactive teaching methods. It is emphasized that the orchestra becomes an environment for developing leadership, communication and pedagogical competencies of a future conductor, as well as a platform for developing creative thinking, artistic intuition and the ability to interpret musical text. Examples of using virtual conducting simulators, online platforms for joint analysis of scores and augmented reality technologies to simulate the rehearsal process are presented. It is shown that the combination of traditional and innovative forms of work in the orchestra opens up new prospects for the professional training of conductors in pedagogical universities and allows taking the learning process to a qualitatively different level.
Keywords: Orchestra, musical conducting, creative laboratory, educational technologies, collective music-making, pedagogical training, digital environment, virtual simulators, creative development.